2019
DOI: 10.1177/0883073819864516
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-sectional Study of the Clinical Profile of Children With Cerebral Palsy in Benin, a West African Low-Income Country

Abstract: Cerebral palsy is a common cause of pediatric motor disability. Although there are increasing amounts of data on the clinical profile of children with cerebral palsy in high-income countries, corresponding information about low-income countries and developing countries is lacking. Therefore, we aimed to describe the clinical spectrum of cerebral palsy in children in Benin, a representative West African low-income country. Our cross-sectional observational study included 114 children with cerebral palsy recruit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 37 publications
0
13
1
Order By: Relevance
“…In Ghana, for example, one study found that the standard mortality rate of children with CP is six times that of the average Ghanaian child without a disability and 15 times that of the average child without a disability in a low-and-middle-income country [17]. According to another study, along with most CLWCPs having severe forms of the disease, Benin also has a high prevalence (17%) of the rare post-neonatal type of CP and low school attendance among its CP population [18]. Uganda similarly has high rates (25%) of postnatal cerebral palsy, largely attributed to infectious causes, which highlights the disproportionate disease burden and factors influencing low resource settings [19].…”
Section: Introductionmentioning
confidence: 96%
“…In Ghana, for example, one study found that the standard mortality rate of children with CP is six times that of the average Ghanaian child without a disability and 15 times that of the average child without a disability in a low-and-middle-income country [17]. According to another study, along with most CLWCPs having severe forms of the disease, Benin also has a high prevalence (17%) of the rare post-neonatal type of CP and low school attendance among its CP population [18]. Uganda similarly has high rates (25%) of postnatal cerebral palsy, largely attributed to infectious causes, which highlights the disproportionate disease burden and factors influencing low resource settings [19].…”
Section: Introductionmentioning
confidence: 96%
“…CP is more prevalent in low and middle-income countries such as Benin than in high-income countries; clinicallybased studies highlight the higher proportion of children in low and middle-income countries presenting a moderate-to-severe bilateral form of the disability. [5][6][7] Nonetheless, access to rehabilitation care in sub-Saharan West Africa is limited by several factors, such as the sparsity of existing rehabilitation services, their concentration in urban settings, general lack of knowledge of caregivers about CP and issues related to stigmatisation and household finances. 21 23 Moreover, such rehabilitation care that is available in Africa remains based to a remarkable extent on non-evidence-based approaches, that is, passive hands-on treatments such as stretching, joint mobilisation and traditional neurodevelopmental therapies.…”
Section: Discussionmentioning
confidence: 99%
“…4 Moreover, up to 70% of children with CP admitted in clinical settings in sub-Saharan Africa present the bilateral type of CP, and are classified as having moderate-to-severe impairment, that is, levels III to V of the GMFCS. [5][6][7] Progress in the paediatrics rehabilitation field during the last decades, has led to investigations mainly in highincome countries of intensive therapies based on motor skill learning principles, which have shown promising efficacy to improve the motor function in children with CP. 8 The relevant motor skill learning principles call for high repetition of child-initiated active movements, a progressive increase of task difficulty or complexity (shaping), a motivating environment entailing tasks of a child-friendly nature and positive reinforcements from therapists.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, two cross-sectional studies from Benin in West Africa, and Uganda in East Africa, indicated prematurity as a risk factor in only 7% and 13%, respectively, of their CP cohorts. [25,26] A recent population-based study on the clinical features and aetiology of CP in Nigeria published in 2020, reported premature birth in 8% of their cohort. [27] Although the present analysis indicated a higher rate of prematurity (31%), it is less in comparison with the Pan-European cohort reported by Horber et al [19] (41%) and the systematic review by Franki et al (44%).…”
Section: Researchmentioning
confidence: 99%